Phase analysis and corrosion behavior of brazing Cu/Al dissimilar metal joint with BAl88Si filler metal - Yu Hua (De Gruyter, 2021)
To meet the requirements of automatic production, a new type of green BAl88Si cored solder was developed. The lap brazing experiments were carried out with copper and aluminum as brazing substrates. The microstructure, phase composition, and corrosion behavior of solder joint interface were studied by field emission scanning electron microscopy, energy dispersive spectroscopy, transmission electron microscopy, electron backscattering diffraction, tensile testing machine, and electrochemical workstation. The results show that the brazing joint of Cu/BAl88Si/Al is metallurgical bonding, and the brazing joint of Cu/BAl88Si/Al is composed of Cu9Al4, CuAl2, a-Al, (CuAl2 + a-Al + Si) ternary eutectic. In addition, there is no obvious preference for each grain in the brazing joint, and there are S texture {123}<634>, Copper texture {112}<111>, and Brass texture {110}<112>. The interface of Cu9Al4/CuAl2 is a non-coherent crystal plane and does not have good lattice matching. The average particle size of CuAl2 is 11.95 µm and that of Al is 28.3 µm. However, the kernel average misorientation (KAM) value at the brazed joint interface is obviously higher than that at the brazed joint interface copper, so the defect density at the brazed joint interface aluminum is higher than that at the brazed joint interface copper. At the same time, due to poor corrosion resistance at the interface on the aluminum side of the brazed joint, serious corrosion spots and corrosion cracks occur at the same time, which leads to the shear performance of the brazed joint decreasing by about 75% after salt spray test for 240 h.